Autonomous Decision-Making and Agentic AI: Challenges and Prospects for Cyber Law - Sayid Muhammad Rifki Noval; Irma Rachmawati; Ahmad Jamaludin; Deden Sumantry; Mohd Zakhiri Md Nor (Universitas Negeri Semarang, 2026)
Artificial intelligence's (AI) explosive growth, particularly in the form of Automated Decision Making (ADM) and Agentic AI, has brought significant changes across various sectors of life, while simultaneously posing complex legal and ethical challenges. This paper evaluates AI regulation and governance from the viewpoint on protection of consumers and cyber legislation, with an emphasis on Indonesia, which is striving to integrate this technology into the legal system and public policy. The findings reveal that Indonesia’s current AI-related regulations remain fragmented and insufficient to handle the regulatory dangers that progressively autonomous AI systems bring. This study examines several cases that illustrate the negative impacts of AI, such as algorithmic errors in the credit system in Germany that resulted in injustices for many individuals, as well as the social assistance distribution scandal in the Netherlands that had serious social and political implications. Concurrently, AI Act was adopted by the European Union as a significant regulatory advance that introduced a risk-based framework to increase accountability, transparency and human oversight in AI governance. Additionally, the controversy surrounding moral problems use AI in the US judiciary related to mass surveillance were also critically analyzed. Analysis of the existing regulations, including the Data Protection Law, the Digital Information and Transactions Law, and the Indonesian government's ethical policies, identifies deficiencies that need to be addressed through adaptive and holistic regulations. The concept of computational accountability and the adoption of international regulations as the Product Liability Directive (PLD) and the AI Liability Directive (AILD) are proposed through a normative juridical analysis, as mechanisms to strengthen accountability and legal protection. This paper also highlights the significance of clarification, openness, and awareness of new rights in the setting of increasingly autonomous and adaptive AI.